Design of an Android-Based Product Ordering Application in The Bakery Industry Using Multimedia Development Life Cycle Method - Aniza Nur Madyanti; Nessa Ananda; Monanda Wandita Rini; Samsul Rizal (Westscience Press, 2025)
The bakery industry in Indonesia shows increasing development. One of the activities carried out by this industry is processing customer orders. Currently, there are still bakery industries where customers order products manually, either by coming directly or by using a telephone or WhatsApp. Manual product ordering causes several problems that can hinder business activities and will have an impact on customer service. This study aims to design an Android-based product ordering application in the bakery industry. The application design uses the Multimedia Development Life Cycle (MDLC) method. The application design stage consists of six stages, namely concept, design, material collecting, manufacturing, testing, and distribution. The results of this study are in the form of an Android-based product ordering application that uses multimedia to provide detailed information related to products and has interactive features to respond to customers quickly. In addition, this application can also generate a summary report of customer orders via the Dashboard. The application that has been designed is expected to support bakery industry players to manage and monitor product ordering performance and improve customer service.